Determination of brown planthopper resistant genes in some rice varieties by molecular markers - Liên, Nguyễn Thị Kim; Hoàng, Nguyễn Huy; Việt, Lê Bắc; Thu, Phan Thị Bích; Chung, Nguyễn Huy (Vietnam Journal of Biotechnology, 2016)
Brown plant hopper (Nilaparvata lugens Stal.) is the one of dangerous pests for rice that were reported in most of rice growing countries. Twenty seven BPH resistance genes have been detected in cultivated and wild rice. However, each resistance gene is able to resist with only strain or certain biotype. Besides, many studies indicated that the toxicity of BPH strains tend to change and loss the resistance of rice lines. The breeding of rice varieties that resist to many BPH biotypes is being the breeders towards. With helping of the development of molecular markers and genetic engineering, the breeders are hopping to identify the molecular markers that linked tightly with BPH resistance genes and develop the rice varieties can gather many resistance genes in a well genomic platform. In this study, we assessed the resistance of rice lines of Vietnam and imported rice lines. The resistance was ditermined by using assessement method in the galvanized box and molecular markers linkage with resistance genes (Bph1, bph2, Bph3, Bph9 and Bph17). The results showed that there was a high affinity between the two methods with 70.59% and 86.27% of lines that have the resistance (respectively). Among of 51 surveyed rice lines, 44 lines (86.27%) were determined to have at least one marker linkage with resistance genes. 19 lines (37.25%) harbored two or three markers linkage with resistance genes. These lines will be a good genetic resource for screening and breeding the resistant rice varieties